2021
DOI: 10.1371/journal.pone.0256083
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity, visceral adiposity, and sarcopenia with an increased risk of metabolic syndrome: A retrospective study

Abstract: Aims Metabolic syndrome (MS) is a global health problem associated with an increased risk of diabetes mellitus (DM), cardiovascular disease (CVD), and cancer. Body composition parameters, including obesity, visceral adiposity, and sarcopenia contribute to the development of MS and CVD. Previous studies have investigated the association of individual body composition parameters with MS. Studies analyzing the association between multiple body composition parameters and MS have been rare. We aimed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…This cost has undoubtedly risen even more due to the aging population, and it is suggested that more high-quality research utilizing cost-effective strategies to counteract these effects is warranted [ 3 ]. Further, several scientific studies have demonstrated the association of sarcopenia with metabolic function and inflammation [ 4 , 5 , 6 , 7 , 8 ]. Chronic low-grade inflammation associated with aging (i.e., ‘inflammaging’) is known to precipitate metabolic syndrome, which may have a reciprocal function in perpetuating the ‘inflammaging’, creating a vicious cycle leading to skeletal muscle mass loss due to the catabolic activity of pro-inflammatory mediators [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This cost has undoubtedly risen even more due to the aging population, and it is suggested that more high-quality research utilizing cost-effective strategies to counteract these effects is warranted [ 3 ]. Further, several scientific studies have demonstrated the association of sarcopenia with metabolic function and inflammation [ 4 , 5 , 6 , 7 , 8 ]. Chronic low-grade inflammation associated with aging (i.e., ‘inflammaging’) is known to precipitate metabolic syndrome, which may have a reciprocal function in perpetuating the ‘inflammaging’, creating a vicious cycle leading to skeletal muscle mass loss due to the catabolic activity of pro-inflammatory mediators [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It participates in a variety of physiological processes and is of great significance to the life activities of the body. Abnormal adipocyte metabolism and metabolic disorders have become epidemics in various countries around the world [ 1 , 2 ], and can cause metabolic syndromes, including obesity, hepatic steatosis, adipose tissue dysfunction, atherosclerosis, and type 2 diabetes [ 3 , 4 ]. Studies have shown that peroxisome proliferator-activated receptor γ (PPARγ) [ 5 ], CCAAT/enhancer-binding protein (C/EBPα) [ 6 ], and the sterol regulatory element-binding protein (SREBP) family [ 7 ] participate in the adipocyte metabolism regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In nearly a decade of research, we have observed that VFA is a more re ective indicator of physical health and cardiometabolic diseases as opposed to BMI, or waist-to-hip ratio [22,23] . Meanwhile, the accumulation of visceral fat was the major contributor to IR [24] .…”
Section: Discussionmentioning
confidence: 99%